Communication Behavior of Farmers in Accessing Information on Banana Cultivation in the Industrial Revolution 4.0 - Okta Hermawati Surya; Sriroso Satmoko; Agus Subhan Prasetyo (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Agricultural information plays an important role in agricultural sector. Information is used as the main source in making top-down decisions. Farmers can access information from both formal and informal sources. Farmers' decisions in accessing information according to their needs and reliable sources are influenced by farmer communication behavior. This study aims to analyze and describe the communication behavior and barriers of farmers in accessing information on banana cultivation in order to compete in global market. This research was conducted in December 2019-January 2020 at Bareng Mukti Farmer Group, located in Ponggok Hamlet, Sidomulyo Village, Bambanglipuro District, Bantul Regency, Special Region of Yogyakarta. This study surveyed ten informants from active members and administrators. The data were analyzed using descriptive qualitative analysis with Miles and Huberman analysis model. The results shows that farmers are still being passive in accessing information on banana cultivation and lack of awareness about the latest communication technology.